Potential gross and net N2O production by the gut of different termite species are related to the abundance of nitrifier and denitrifier groups - Miambi, Edouard; Jusselme, Thi My Dung; Châtelliers, Charline Creuzé des; Robert, Alain; Delort, Abigail; Le Roux, Xavier (Frontiers in Microbiomes, 2022)
Termites can be a significant source of N2O emissions in tropical and subtropical ecosystems. The emission rates vary greatly between species, with many species creating emission hot spots while others act as net sinks. We studied the relationships between net and gross N2O production/consumption and the abundances of eight nitrifier and denitrifier groups (assessed through functional marker genes) in termite gut homogenates for eleven species from five feeding guilds. Overall, gross N2O production was strongly correlated with the abundance of nitrite reducers and, to a lesser extent, nitrifiers in the gut, while N2O reduction was correlated with the abundance of nosZ1 N2O reducers and the nosZ1/nirK ratio. Our results show that the considerable differences in gross and net N2O production between termite species are mainly due to the differences in the abundances of nitrifiers and denitrifiers and the balance between them. N2O production rates by live individuals measured for a subset of termite species were lower in the wood-feeding than in other species. Our results suggest that the differences in abundances could depend on the feeding guild, although this should be tested on a larger number of species.